Synergistic Effects of Linderanolide B Combined with Arbutin, PTU or Kojic Acid on Tyrosinase Inhibition - Hseu, You-Cheng; Cheng, Kuo-Chen; Lin, Yi-Chieh; Chen, Chung-Yi; Chou, Hsin-Yu; Ma, Dik-Lung; Leung, Chung-Hang; Wen, Zhi-Hong; D. Wang, Hui-Min (Current Pharmaceutical Biotechnology, 2015)
Melanin uncontrollable accumulation is a serious social problem to not only women, but also men, and causes pigment over-expression disorders such as freckles, melasma or pigmented acne scars. The synergism is used widely in medication, and the effectiveness makes the drug applications more valuable. Within this experiment, three well-known compounds were chosen: kojic acid, 1-phenyl-2-thiourea (PTU) and arbutin, and they were combined individually with our substance linderanolide B, which is purified from Cinnamomum subavenium. Hence, deciphering the synergistic action of possible whitening agents was the goal of this study. The tyrosinase activity, melanin content, and the combination index (CI) values were observed in B16F10 cells, in addition, the consequences were detected by isobologram analysis. We discovered that certain melanin inhibitors showed synergistic properties when they were combined together to suppress tyrosinase activities. As a result, linderanolide B has a potential synergy on tyrosinase inhibition, and it can be used widely in cosmetic and medication industries.
Keywords: Melanin